Identifying the main aspects of analysing the condition of the historic city's living environment (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2025)
The article considers the basic principles of analysing the state of the living environment of a historical city with a view to its improvement, identifies its components and creates models for each aspect of the analysis. Characterisation of the causes and extent of changes and transformations in the structure of rural areas is an important task for developing a strategy for creating conditions for further fruitful and full development of the city.The study is aimed at summarising and structuring various information on the reconstruction object, identifying the aspects by which the existing state of residential and public development zones should be assessed, in order to determine the potential and capabilities of the territory to accept reconstruction measures.The study of public needs, current trends and available resources will contribute to the optimisation of urban planning conditions in accordance with social, environmental, ergonomic, functional, aesthetic, constructive, technological and economic requirements for improving the living environment. The improvement of the urban structure to achieve the physical, psychological and spiritual comfort of a person in an artificial environment demonstrates a human-centred approach to the search for an integrated, comprehensive (economic, social, energy, economic, transport, etc.) model of a city with a high level of environmental quality.Urban redevelopment in the 21st century is characterised by an integrated approach. It is based on the mandatory consideration of biological, physiological, spiritual, aesthetic, psychological and socio-cultural aspects of human needs. It is important to emphasise the importance of social, environmental, ergonomic, functional, aesthetic, constructive, technological and economic requirements in improving the living environment and the need to ensure the conditions for the creation of an ecologically, psychologically and aesthetically comfortable environment by means of urban planning.Determination of the existing structural and planning features of the organisation of residential and public areas of a historical city, the main factors influencing their formation in new social conditions, the availability of reserves and potentials, and trends for their further improvement is an important task of urban planning for development of a strategy for creation of conditions for fruitful and full, sustainable development of the city with ensuring a high quality human living environment.Determining the principles of the analysis of the state of the living environment of a historical city will help to obtain comprehensive information for the development of a programme for the further development of residential and public areas of Ukrainian cities, their reconstruction and transformation into a comfortable, dignified and safe environment that meets the level of human needs and expectations as much as possible.
Keywords: zones of residential and public development; comfort of living environment; reconstruction; human needs and physiological capabilities; urban development needs